Pengaruh Kepemimpinan Autentik dan Komitmen Afektif terhadap Kinerja Guru pada MAS Berbasis Pondok Pesantren di Kota Tangerang Selatan - Jamilah Muryati; Aris Munandar; Naufal Hilmizen; Endang Koswara; Agus Mulyanto; Elis Lisyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine and analyze the problem as the variable studied, according to the hypothesis being tested, namely: (1) There is a direct influence of the principal's authentic leadership on teacher performance, (2) There is a direct influence of teacher affective commitment on teacher performance, and ( 3) There is a direct influence of the principal's authentic leadership on teacher affective commitment. The research method is a quantitative method and was carried out on Islamic boarding school-based MAS teachers in South Tangerang City, a population of 133 teachers with a research sample of 53 teachers selected by random sampling. The results of this research show: First, there is a positive direct influence of the principal's authentic leadership on teacher performance obtained by the regression equation: = 94,050 + 0,899 X1 path coefficient (р31) = 0.636, so it can be concluded that there is a positive and significant direct influence of the principal's authentic leadership on teacher performance of 40,4%. Second, there is a positive direct influence of teacher affective commitment on teacher performance. The regression equation is obtained: = 105,930 +0,798 X2 of 35,0%, Third, there is a positive direct influence of the principal's authentic leadership on teachers' affective commitment with the regression equation: = 79,280 + 0,586 X1 path coefficient value (р21) = 0.504, it can be concluded that there is a positive and significant direct influence of the principal's authentic leadership on teachers' affective commitment of 25,4%. Based on the findings of this research, it can be used as useful information for teachers, in particular, and all related parties. As an effort to improve teacher performance through the authentic leadership of school principals and increasing better teacher affective commitment.